2010
DOI: 10.3168/jds.2010-3429
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postpartum uterine diseases in dairy cows

Abstract: The objective of this observational study was to investigate the risk factors for metritis, purulent vaginal discharge, and cytological endometritis. The hypothesis was that purulent vaginal discharge and cytological endometritis would have different risk factors because they represent distinct manifestations of uterine disease. Data generated from 1,363 Holstein cows (3 herds) enrolled in a randomized clinical trial were used. Calving history, periparturient disease incidence, and body condition score at calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
258
5
26

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(335 citation statements)
references
References 34 publications
46
258
5
26
Order By: Relevance
“…Corroborating the results from the present study, others have shown an association between parity and the presence of cystic structures (Erb and Martin, 1980;Zulu and Penny, 1998;Roche, 2006), embryonic death (Santos et al, 2009) as well as a deterioration in uterine health (Dubuc et al, 2010). The increased incidence of cystic structures in older parity cows could be potentially related to their greater milk production and its known effect on the presence of cystic structures (Zulu and Penny, 1998).…”
Section: Paritysupporting
confidence: 82%
See 2 more Smart Citations
“…Corroborating the results from the present study, others have shown an association between parity and the presence of cystic structures (Erb and Martin, 1980;Zulu and Penny, 1998;Roche, 2006), embryonic death (Santos et al, 2009) as well as a deterioration in uterine health (Dubuc et al, 2010). The increased incidence of cystic structures in older parity cows could be potentially related to their greater milk production and its known effect on the presence of cystic structures (Zulu and Penny, 1998).…”
Section: Paritysupporting
confidence: 82%
“…Substantiating the results from the present study (Figure 6), others (El-Din Zain et al, 1995) have shown that uterine involution takes longer in older parity cows. Furthermore, both the incidence and severity of uterine infection is greatest in later parity cows (Erb and Martin, 1980;Dubuc et al, 2010).…”
Section: Paritymentioning
confidence: 99%
See 1 more Smart Citation
“…Em vacas Holandesas, criadas na América do Norte e Europa, a bioquímica sérica tem sido intensamente empregada como ferramenta na prevenção de doenças no periparto (Dubuc et al 2010, Chapinal et al 2011, Roberts et al 2012. Entretanto, em vacas Jersey, especialmente no Brasil, ainda não existem trabalhos que apresentem o perfil metabólico sérico normal de vacas em produção e nem correlacionando com doenças e desempenho reprodutivo pós-parto.…”
Section: Introductionunclassified
“…Moreover, cows that present periparturient diseases are more susceptible to develop other diseases (Opsomer et al 2000; thus, a healthy passage through the transition period is essential for proper reproductive efficiency in dairy cows. The assessment of the impact of gynecological diseases on the overall level of reproductive processes has been well documented in European dairy cattle in temperate climates (Dubuc et al 2010, Gilbert 2011. A great number of these studies were carried out in herds with two milkings per day, without the use of recombinant bovine somatotropin (rbST) throughout lactation and at latitudes where heat load is not a serious hurdle for dairy operations.…”
Section: Introductionmentioning
confidence: 99%